Four new species of the spider genus Cicurina Menge, 1871 from China (Araneae: Dictynidae) - Wang, Lu-Yu; Zhou, Gu-Chun; Peng, Xian-Jin (Zootaxa, 2019)
Four new species of the genus Cicurina are described: C. daweishanensis spec. nov. (female), C. kekei spec. nov. (male and female), C. lichuanensis spec. nov. (male and female) and C. yuelushanensis spec. nov. (male and female). Photos of body and copulatory organs, line drawings of copulatory organs, as well as the locality map are provided. The type specimens of Cicurina eburnata Wang, 1994 were reexamined for the comparison of allied species. Photos of C. calyciforma Wang & Xu, 1989 are also presented in order to compare it with two new species.